Supermarket - Azuchi, Satoshi 1937- (Thomas Dunne Books, 2009)
After he resigns from his elite banking job to help a cousin manage a supermarket in post-World War II Japan, Kojima is challenged by a woman from his childhood to consider whether his business goals are worth his efforts.